(untitled) (Baghdad Science Journal, 2025)
The anatomic characteristics of the leaves of 22 taxa of Stachys L. representing seven of the currently recognized sections distributed in northern Iraq, were examined. The study did not found any variations in the characteristics of the stomata system of the leaves.Therewere variations with a good taxonomic value in other anatomic characteristics.Thevariations in characters of the mesophyll tissue in S.kurdica var.brevidens Bom ex Bhattacharjeewas bifacial but in S.kurdica var.kurdica Boiss. & Hohen.was unifacial .The study also found that the taxa S.benthamiana Bioss., S.lanigera (Bornm.) Rech.f. andS.kotscyi Bioss. with 3 vascular bundles in the middle vein while the taxa S.ballotiformis Vatke., S.megalodonta Hausskn. &Bornm.exP.H.Davis and S.kurdica with one only. The spescies S.lavandulifoliaVahle.had a cross section of V shape that did not seen in other studied taxa. The results showed evidence were useful in separating between species within the same section.